Effectiveness gynura procumbens on blood cholesterol levels in a rat model of diet-induced hypercholesterolemia - Sri Wahyuni Gayatri; Priyo Sasmito; Aryanti Bamachry (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Gynura procumbens (Lour.) is a medicinal plant known for its potential in managing various metabolic disorders, including hypercholesterolemia. However, scientific data supporting its cholesterol-lowering effects remains limited. Purpose: To evaluate the effect of ethanol extract of Gynura procumbens leaves on total cholesterol levels in male Wistar rats induced with a high-fat diet. Method: A quasy experiment approach, specially focusing on post-test only group. The study took place from March-August 2023, in Research Laboratory of the Faculty of Medicine, Universitas Muslim Indonesia. The independent variable was gynura procumbens extract dependent variables is total cholesterol levels. Using purposive sampling and federer formula, 21 participants were selected which were divided into 3 groups. Group I (negative control) received a placebo, group II (treatment group) received gynura procumbens extract, and group III (positive control) received simvastatin, who met specific inclusion and exclusion criteria. Analysis proceeded with a univariate test to determine the frequency distribution of respondent’s characteristics, followed by bivariate analysis using man whitney and anova test. Results: After induction, all groups showed a marked increase in cholesterol levels. Following the treatment period, the group receiving Gynura procumbens extract demonstrated a significant reduction in cholesterol levels (123.43 ± 24.80 mg/dl, p = 0.018), which was statistically comparable to the simvastatin group (112.83 ± 8.52 mg/dl, p = 0.033). In contrast, the negative control group showed no significant change (231.33 ± 90.56 mg/dl, p = 0.075). Conclusion: These findings indicate that Gynura procumbens leaf ethanol extract has a significant cholesterol-lowering effect in hypercholesterolemic rats, with efficacy comparable to simvastatin as standard pharmacological therapy.